Tafsir Ayat Al-Quran sebagai Pendidik - Indah Rama Sahara; Tiffani Asnita Putri; Panyahatan Rasoki Siregar; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study examines the role of interpretation of Qur'anic verses as an educational instrument in the context of contemporary Islamic learning. Through literature analysis and case studies, this study explores how the interpretation of Quranic verses can serve as an effective pedagogical tool in transmitting moral, ethical, and spiritual values to students. The main focus is given on the methodology of interpretation that is relevant to the needs of modern education, as well as its impact on the understanding and internalization of Islamic teachings by the younger generation. The results of the study show that a contextual and integrative interpretation approach has significant potential in increasing the effectiveness of Islamic education. These findings highlight the importance of adapting traditional interpretation methods to contemporary pedagogical approaches to create more meaningful and relevant learning experiences. The implications of this research include recommendations for the development of a more holistic and responsive Islamic education curriculum to the challenges of the times, as well as teacher training in using the interpretation of the Quran as a dynamic and transformative educational tool.